Haematopoietic stem cell transplant in cutaneous T‐cell lymphomas: A multicentre propensity‐score matched study - Bejarano, Lía; Grau‐Pérez, Mercè; Paíno‐Román, Marina; Muret, María Pilar García; Morillo, Mercedes; Muniesa, Cristina; Torre‐Castro, Juan; Estrach, M. Teresa; Díez, Elena Amutio; Belloso, Rosa Mª Lzu; Peñate, Yeray; Martínez‐Mera, Constanza; et al. (Journal of the European Academy of Dermatology and Venereology, 2025)
Advanced cutaneous T-cell lymphomas (CTCL) are rare, generally refractory to therapeutic options, and have a poor prognosis. Haematopoietic stem cell transplantation (HSCT), mainly allogeneic HSCT (allo-HSCT), is considered a potentially curative option in CTCL refractory to other therapies. However, around half of patients relapse, and allo-HSCT is associated with significant adverse events. The available evidence on the usefulness of HSCT in CTCL generally comes from isolated cases and case series with a limited number of patients. Our aim was to evaluate the outcome of patients undergoing HSCT for advanced primary CTCL in Spain in a real-world environment and to compare their survival with that of similar patients who did not receive HSCT. We performed a retrospective observational study nested within the Primary Cutaneous Lymphoma Registry (RELCP) of the Spanish Academy of Dermatology and Venereology, collecting data on all patients receiving HSCT. Then, we performed propensity score matching (PSM) to pair HSCT patients with non-HSCT patients, adjusting for diagnosis, highest disease stage and age at diagnosis. We then performed survival analysis by means of Cox regression. Of 2848 patients included in the RELCP, 51 patients underwent HSCT. Thirty-six patients (70.6%) achieved a complete response and seven patients (13.7%) partial response. Relapse was developed by 56.9% of patients, and 39.2% died (19.6% due to disease progression and 15.7% due to HSCT complications, mainly graft-versus-host disease (GVHD) and sepsis). Overall survival (OS) after HSCT at 5 years was 58.9%. No differences in OS were found between HSCT and non-HSCT groups. We did not observe a survival benefit among HSCT patients compared to non-HSCT patients within the RELCP cohort. This could be due to patients having received a mean of 6.3 lines of treatment before HSCT. Larger studies might help identify subgroups of patients who might benefit from HSCT.